TRANSITIVITY AS AN INDICATOR OF STUDENTS' RECOUNT WRITING - Dianita Dianita (Universitas Widyatama, 2023)
This study investigated the transitivity process found in students' recount text and the prevalent transitivity process. The descriptive qualitative research method assesses the Transitivity Process of students constructing recount texts, which involves data collection, classification, analysis, and interpretation. This study's document includes eleven students authoring recount texts and 603 data comprising clauses chosen from the text. Following the results, in students' recount text, there are six types of transitivity processes: material process, relational process, mental process, linguistic process, existential process, and behavioral process. The material process is the most used, accounting for 390 (64.67%) of all occurrences in the overall data. The relational method is the second most widely used, accounting for 90 (14.92%) events in the data. The mental process is the third most used, accounting for 72 (11.94%) occurrences in the overall data. The behavioral process is used with 21 (3.48%) occurrences from the actual data. In comparison, the verbal process is used with 15 (2.48%) of the total data, while the existential process is used with 15 (2.48%). The most common transitivity process type in all students' recount texts, accounting for 390 events, is Material Process.